Assessing the role of school management in integrated education in public schools in Mafraq governorate from the point of view of its principals - Hawamdeh, Kholoud Ali (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the "assessment of the role of school administration in blended education in public schools in Mafraq Governorate from the point of view of its principals." A random group consisted of (50) school principals, and it was treated statistically using the statistical package (SPSS) program, where the study concluded that there is a significant role evaluating the role of school administration in blended education in public schools in Mafraq Governorate from the point of view of its principals, a total average of (4.16) out of 5) Any (significant) role, and it was found that there were no statistically significant differences at the significance level (α ≥ 0.05) in the average responses of the study sample members in evaluating the role of school administration in blended education in public schools in Mafraq Governorate from the point of view of its principals according to the study variable (gender, years of experience, educational qualification), and based on the results of this study, the researcher made several recommendations, the most important of which was that school principals in Mafraq Governorate should use modern educational trends for educational leadership as well as pay attention to hybrid learning In secondary schools in Mafraq Governorate schools, in addition to proposals for complementary studies on the subject.
Keywords: Modern Trends; Educational Leadership; Hybrid Learning; Mafraq School Principals